Investigating sensory phenomena and alterations in brain structure in Tourette syndrome using a multi-modality framework - Sigurdsson, Hillmar P. (2019)
Tourette syndrome (TS) is a childhood onset, hyperkinetic movement disorder, characterised by inappropriate motor tics and vocalisations. TS affects approximately 1% of children and adolescents aged 5-18 years, while rates are much lower in young adults. In addition to tics, patients report feelings of uncomfortable inner bodily and cognitive sensations termed premonitory sensory phenomena (PSP), which exacerbate during the inhibition of tics. Furthermore, patients with TS report having increased sensitivity to sensory inputs across all sensory modalities but in the absence of any differences in sensory thresholds measured using objective methods. Most studies to date have measured affective touch thresholds in adult patients only, and therefore limited inference can be made in younger patients. In addition, the neural substrates of PSP are not well understood but possibly emerge due to improper sensorimotor gating mechanisms and altered function of cortico-basal ganglia circuits. The epicentre of this might also be the insular cortex, which is responsible for the detection, awareness and relaying information about sensory input to higher cortical areas. The primary focus of this thesis is on sensory phenomena and the alteration in brain structure in young people with TS, and is laid out in 4 experimental chapters. Using a multi-modal framework this work had two aims. The first aim was to investigate if and why young patients with TS demonstrate sensory amplification to sensory input. To achieve this, I gathered data on tactile sensory thresholds using a set of Von Frey monofilaments and determined sensory thresholds using psychometric function fitting, and sensitivity and response bias using signal detection theory. Furthermore, I employed transcranial magnetic stimulation (TMS) to ascertain differences in cortical maps between patients and healthy volunteers. Using this data, I was able to make inference of the location, distance between and the size of several muscle representations on the sensorimotor cortex and ask the question if any ‘remapping’ of these representations could explain perceived sensitivity to sensory inputs. The second aim of this thesis was to investigate the relationship between PSP and brain structure. To achieve this, I first acquired data using diffusion tensor imaging (DTI) to make inferences on the structural connectivity of white matter. Secondly, I used high-resolution structural imaging to measure volume of cortical grey matter. Analyses were performed using whole-brain exploratory methods, network-based methods and pattern recognition methods. The results show marked differences on a global scale but also very specific and focal differences in key areas of the brain, which correlated with the frequency and severity of PSP in patients with TS. This thesis concludes with a discussion, which summarises and integrates all results presented. The text is organised according to three major discussion points, and reviews similarities between the present results and the current knowledge of PSP in TS. Moreover, the chapter also briefly discusses the similarities between TS, and the symptoms and the neural substrates of individuals with sensory processing disorders.